Pengaruh Pola Kepemimpinan Dan Budaya Perusahaan Terhadap Produktivitas Kerja Karyawan: Studi Pada CV Hurip Di Kabupaten Ciamis - Jejen Jenal; Oyon Saryono; Irma Darmawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The background of this research is the work productivity of CV Hurip employees, which fluctuates, where there is an increase and there is also a decrease. Employees lack the ability to complete the job. Employees lack the ability to improve work results achieved. Employees do not prioritize quality. The leadership of CV Hurip is responsible, wise, able to manage, direct, influence and understand the wishes of employees. Leaders are able to overcome the problems currently faced by employees. Leaders provide compensation for each employee is still lacking. Thus, the purpose of this study is to know and analyze the influence of leadership patterns on the work productivity of CV Hurip employees in Ciamis Regency. Knowing and analyzing the influence of corporate culture on the work productivity of CV Hurip employees in Ciamis Regency. Knowing and analyzing the influence of leadership patterns and corporate culture on the work productivity of CV Hurip employees in Ciamis Regency. This type of research is an explanatory survey while the data analysis technique is descriptive statistics. Based on the results of the study it was concluded that the pattern of leadership tends to be high, as well as high employee work productivity. This indicates a strong influence of leadership patterns on employee work productivity. This means that if the pattern of leadership increases, it will be followed by an increase in employee work productivity. Company culture tends to be high, as well as high employee work productivity. This indicates a strong influence of corporate culture on employee productivity . This means that if the company's culture increases, it will be followed by an increase in employee work productivity. Leadership patterns and corporate culture tend to be high, as well as high employee work productivity. This indicates a strong influence of leadership patterns and corporate culture on employee productivity. This means that if the pattern of leadership and corporate culture increases, it will be followed by an increase in employee productivity